Green synthesis and characterization of silver nanoparticles using leaf extract of aloe vera - Ojonukpe, Omotoyosi; Ibrahim Olakunle shoetan (IJRDO-Journal of Applied Science, 2020)
For this research, a novel approach has been carried out for the green synthesis of silver Nanoparticle using leaf extract of Aloe Vera and silver nitrate solution. Stable silver nanoparticleswere formed by treating aqueous solution of AgNO 3 with the plant leaf extracts as reducing agentof Ag + to Ag 0 . UV-visible spectroscopy was used to monitor the quantitative formation of silvernanoparticles and this show a peak at 410 nm. The synthesized silver nanoparticles werecharacterized using scanning electron microscopy (SEM) and Fourier Transform Infra-redSpectroscopy (FTIR). The average particle size ranged from 300 to 410 nm. The particle sizecould be controlled by changing the reaction temperature, leaf broth concentration and AgNO 3concentration. This eco-friendly method of synthesizing silver nanoparticles production providesrates of synthesis which is more efficient when compared to those of chemical methods and canapplied in various human endeavours such as cosmetics, foods and medical applications.